EDUKASI PRATIK PIJAT OKSITOSIN SEBAGAI UPAYA PENINGKATAN PRODUKSI AIR SUSU IBU (ASI) DI RW9/RT1, KELURAHAN BULUROKENG KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Fony, Fony; Alam, Hardianti H.P; Senolangi, Trinarti; Bulan, Sahari; Alif, Nur Amalia (Universitas Negeri Makassar, 2025)
Breast milk (ASI) is the primary and most ideal source of nutrition for newborns. However, challenges in breastfeeding such as low milk production and limited knowledge among postpartum mothers about oxytocin massage pose significant concerns. This community service program aimed to improve both knowledge and breast milk production through educational sessions and hands-on practice of oxytocin massage. The methods used included health counseling, demonstration, and evaluation through pre-tests and post-tests. The activity was conducted in RW9/RT1, Bulurokeng Subdistrict, targeting six married couples. The results indicated a significant improvement in participants' knowledge, with the average pre-test score of 30 increasing to 80 in the post-test. Oxytocin massage proved effective in stimulating the release of oxytocin and prolactin hormones, which play key roles in breast milk production. This educational intervention is expected to be implemented sustainably by health cadres and family members to support the success of exclusive breastfeeding.